Bismuth-based composite electrode material and preparation method and application thereof
The preparation of bismuth oxide/bismuth sulfide composite electrode material by hydrothermal method solved the problem of insufficient cyclic stability of bismuth chalcogenide compounds in supercapacitors, and achieved significant improvements in specific capacitance, conductivity and cyclic stability. It is suitable for pseudocapacitor supercapacitors.
Patent Information
- Application Number
- CN202510057672.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-11
AI Technical Summary
Bismuth chalcogenides have insufficient cyclic stability and low conductivity in supercapacitors, which limits their application in the field of supercapacitors.
The bismuth oxide/bismuth sulfide composite electrode material was prepared by hydrothermal method, and a built-in electric field was generated at the composite interface, increasing the specific surface area and conductive channels, and improving conductivity and cyclic stability.
The specific capacitance, conductivity and cyclic stability of bismuth-based composite electrode materials are significantly improved, so that they can show better performance in pseudocapacitor supercapacitors.
Smart Images

Figure CN119811905A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supercapacitors and relates to a bismuth-based composite electrode material and a preparation method and application thereof. Background Art
[0002] Energy is essential for human development. Energy consumption and production that rely on the combustion of fossil fuels will seriously affect the world economy and ecology. Therefore, there is an increasing demand for environmentally friendly, high-performance renewable energy storage devices. Electrochemical energy is an inevitable part of the clean energy mix. Batteries, supercapacitors and fuel cells are unconventional energy devices that use the principle of electrochemical energy conversion. Supercapacitors have attracted widespread attention due to their high specific capacitance, long life cycle, high power density, almost no maintenance, no memory effect, safety, and as a bridge between the power-energy difference between capacitors and fuel cells / batteries. The emergence of supercapacitors provides a feasible solution for providing energy in rural areas due to the lack of public power grids and the high cost of wiring and power supply. Supercapacitors can also be used as power sources for mobile devices such as mobile phones, laptops, digital cameras, etc. In electric and hybrid vehicles, supercapacitors can be used to provide the high power density required for short-term acceleration and energy recovery devices during emergency braking, thereby saving energy.
[0003] Supercapacitors are divided into pseudocapacitors and double-layer capacitors. Double-layer capacitors are based on the physical separation and storage of charges, and are adsorbed by electrostatic charges in the double layer that spontaneously forms at the electrode-electrolyte interface. Carbon materials are the most widely used. Pseudocapacitors, in addition to the physical charge storage mechanism, also rely on fast reversible redox reactions on or near the surface of active materials in the electrode to store charge. Pseudocapacitors have higher power storage potential than double-layer capacitors.
[0004] Bismuth chalcogenide (Bi 2 X 3 , X=O, Se, S, Te) refers to compounds composed of Bi and Group VI elements, Bi 2 X 3 The inherent properties of Bi, such as the ability to transport ions, narrow band gap, and environmental friendliness, make it an ideal material for energy-related applications in related industries. Chalcogenides are particularly suitable for energy storage applications due to their structural gaps and tendency to form alloys. However, Bi 2 X 3 The cycling stability of the electrode is insufficient and the conductivity is low. The electrical and electronic properties of bismuth chalcogenides depend on their surface morphology, crystal structure, size, etc.
[0005] The application of bismuth-based materials in the field of supercapacitors is limited largely due to their poor specific capacitance and low cycle stability. Therefore, most of the research focuses on mixing bismuth-based materials with highly conductive carbon materials and changing the morphology of the materials or introducing defects in the design to increase their contact active sites. For example, the existing patent CN202010399834.X discloses an α-Bi 2 O 3 Supercapacitor electrode material loaded with carbon material and preparation method thereof, Bi 2 O 3 The loaded carbon material effectively improves the conductivity, but its Bi 2 O 3 The load on the carbon material is simply combined, and under high current density environment, the material is prone to dissociation, causing the material to collapse and thus affecting its stability and reversibility.
[0006] Therefore, it is necessary to provide a bismuth-based composite electrode material and a preparation method and application thereof to improve the specific capacitance and cycle stability of the bismuth-based composite electrode material. Summary of the invention
[0007] In order to overcome the problems in the background technology, the present invention prepares a bismuth-based composite electrode material composed of bismuth oxide / bismuth sulfide by a hydrothermal method, generates a built-in electric field at the bismuth oxide / bismuth sulfide composite interface, contributes additional electrons, and produces high conductivity. At the same time, the bismuth-based composite electrode material has a larger specific surface area, and the conductive channel of the bismuth-based composite material is increased, thereby effectively improving the specific capacitance, cycle stability and conductivity of the bismuth-based composite electrode material, so that after the bismuth-based composite electrode material is used as a positive electrode material in a pseudocapacitor supercapacitor, the pseudocapacitor supercapacitor has better performance.
[0008] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0009] In one aspect, the present invention provides a method for preparing a bismuth-based composite electrode material, the preparation method comprising the following steps:
[0010] (1) Sodium sulfide nonahydrate is dissolved in water, and magnetic stirring is performed for 20-40 min (preferably 30 min) or ultrasonic oscillation is performed for 40-120 min to obtain a solution I, and bismuth oxide powder is added to the solution I to perform a hydrothermal reaction to obtain a reaction product.
[0011] (2) Centrifuging the reaction product obtained in step (1) to obtain a precipitate I, cyclically oscillating and centrifuging the precipitate I, and then drying the solid product obtained after centrifugation to obtain a bismuth-based composite electrode material.
[0012] Preferably, in step (1), the concentration of solution I is 0.01 mol / L, and after bismuth oxide powder is added to solution I, the molar ratio of bismuth to sulfur in solution I satisfies bismuth:sulfur>1.
[0013] Preferably, in step (1), the hydrothermal reaction temperature is 160° C. and the reaction time is 720 min.
[0014] Preferably, in step (2), deionized water and anhydrous ethanol are used alternately to oscillate and centrifuge the precipitate I until the supernatant is neutral after centrifugation. For example, deionized water is first used as a solvent to oscillate and centrifuge the precipitate I, the centrifuge speed is 8000-10000 rpm, preferably 8000 rpm, each centrifugation time is 8-15 min, preferably 10 min, each oscillation time is 10 min, after centrifugation, deionized water is replaced with anhydrous ethanol as a solvent, and the precipitate I is oscillated and centrifuged again under the same conditions, and then the anhydrous ethanol is replaced with deionized water as a solvent, and the precipitate I is oscillated and centrifuged under the same conditions, and the deionized water and anhydrous ethanol are used as solvents to oscillate and centrifuge the reaction product in a cycle until the supernatant is neutral after centrifugation.
[0015] Preferably, the bismuth oxide powder is prepared by the following steps:
[0016] S1: adding bismuth nitrate pentahydrate to nitric acid and stirring to obtain solution II. After adding bismuth nitrate pentahydrate to nitric acid, stirring by magnetic force for 20-40 minutes (preferably 30 minutes) or using ultrasonic vibration for 40-120 minutes to make solution II uniform.
[0017] S2: Under stirring, KOH solution is added dropwise to the solution II obtained in step S1 to adjust the pH of the solution II to 11.0-14.0, preferably pH=12.0.
[0018] S3: subjecting the solution II, which has been pH-adjusted in step S2, to a hydrothermal reaction to obtain a reaction product. Before subjecting the solution II to a hydrothermal reaction, subjecting the solution II to magnetic stirring for 20-40 minutes (preferably 30 minutes) or ultrasonic oscillation for 40-120 minutes.
[0019] S4: centrifuging the reaction product obtained in step S3 to obtain a precipitate II, and alternately oscillating and centrifuging the precipitate II with deionized water and anhydrous ethanol until the supernatant after centrifugation is neutral, and drying the solid product obtained after centrifugation to obtain bismuth oxide powder.
[0020] Preferably, in step S1, the concentration of nitric acid is 0.8 mol / L-1.5 mol / L, preferably 1 mol / L, and the solid-liquid ratio of bismuth nitrate pentahydrate to nitric acid is bismuth nitrate pentahydrate: nitric acid = 0.485 g: 1 mL.
[0021] Preferably, in step S2, the concentration of the KOH solution is 0.8 mol / L-5 mol / L, preferably 1 mol / L.
[0022] Preferably, in step S3, the hydrothermal reaction temperature is 120° C. and the reaction time is 720 min.
[0023] On the other hand, the present invention proposes a bismuth-based composite electrode material, which is prepared by the above-mentioned preparation method. The bismuth-based composite electrode material is a composite of bismuth oxide / bismuth sulfide. The built-in electric field generated at the load interface contributes additional electrons to produce high conductivity.
[0024] The present invention also proposes applying the bismuth-based composite electrode material to a pseudocapacitor supercapacitor, wherein the bismuth-based composite electrode material serves as a positive electrode material of the pseudocapacitor supercapacitor.
[0025] The pseudocapacitive supercapacitor can be prepared by the following steps:
[0026] Q1: The bismuth-based composite electrode material, conductive carbon black, and polyvinylidene fluoride are mixed evenly in a mass ratio of bismuth-based composite electrode material: conductive carbon black: polyvinylidene fluoride = 8:1:1-8:2:2 to obtain a mixture, and N-methylpyrrolidone (NMP) is added to the mixture to obtain a slurry, and N-methylpyrrolidone is added until the slurry can be attached to the wall. The slurry is mixed evenly by magnetic stirring for 8-12 hours or manual grinding for 45-60 minutes.
[0027] Q2: Use a homogenizer to spin-coat the slurry obtained in step Q1 onto the nickel foam, and use a tablet press to press the tablet for 30 seconds at 8-10 MPa to obtain an electrode sheet.
[0028] Q3: Use the electrode sheet as the positive electrode, activated carbon as the negative electrode, and 5-10M KOH solution as the electrolyte to make a supercapacitor.
[0029] Beneficial effects of the present invention:
[0030] 1. The bismuth oxide / bismuth sulfide composite electrode material prepared by the present invention changes the morphology of bismuth oxide, increases the specific surface area of the composite electrode material, provides more contact sites, and generates a built-in electric field at the composite interface of the composite electrode material, thereby providing more free electrons available for the reaction. In addition, a heterogeneous structure is generated at the composite interface, which shrinks the band gap of the composite electrode material, improves the conductivity and reduces the resistance, thereby effectively improving the specific capacitance, conductivity and cycle stability of the composite electrode material.
[0031] 2. The present invention adopts a two-step hydrothermal method to prepare bismuth oxide powder and bismuth-based composite electrode material respectively. The preparation method is simple, low-cost, easy to achieve mass production, and suitable for industrial promotion and application.
[0032] 3. The bismuth-based composite electrode material of the present invention is applied in a pseudocapacitor supercapacitor as a positive electrode material. Conventional negative electrode materials and electrolytes can be used in combination with the bismuth-based composite electrode material. The bismuth-based composite electrode material of the present invention has good applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope image of the bismuth-based composite electrode material prepared in Example 1 of the present invention;
[0034] Figure 2 This is the XRD pattern of the bismuth-based composite electrode material prepared in Example 1 of the present invention;
[0035] Figure 3 This is a CV graph of the bismuth-based composite electrode material prepared in Example 1 of the present invention in a three-electrode environment;
[0036] Figure 4 This is a CP diagram of the bismuth-based composite electrode material prepared in Example 1 of the present invention under a three-electrode environment;
[0037] Figure 5 The cycle stability diagram of the electrode materials prepared in Example 1 of the present invention and Comparative Example 1;
[0038] Figure 6 This is a scanning electron microscope image of the electrode material prepared in Comparative Example 1 of the present invention;
[0039] Figure 7 This is the XRD diagram of the electrode material prepared in Comparative Example 1 of the present invention;
[0040] Figure 8 This is a CV graph of the electrode material prepared in Comparative Example 1 of the present invention in a three-electrode environment;
[0041] Fig. 9 This is a CP diagram of the electrode material prepared in Comparative Example 1 of the present invention in a three-electrode environment;
[0042] Fig.10 This is a CV graph of the electrode material prepared in Comparative Example 2 of the present invention in a three-electrode environment;
[0043] Fig.11 This is the CP diagram of the electrode material prepared in Comparative Example 2 of the present invention in a three-electrode environment. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the described contents.
[0045] Example 1
[0046] In this embodiment, bismuth-based composite electrode materials are prepared by the following method:
[0047] (1) 4.85 g of bismuth nitrate pentahydrate was placed in 10 ml of 1 mol / L nitric acid and stirred with a magnetic stirrer for 30 min to obtain a solution II.
[0048] (2) While the above solution II is being stirred, a 1 mol / L KOH solution is added dropwise to adjust the pH of the solution to 12.
[0049] (3) The solution II after pH adjustment in step (2) was stirred for 30 min using a magnetic stirrer, and then the solution II was transferred to a reaction kettle. The reaction kettle was placed in an oven and heated at a constant temperature of 120° C. for 720 min.
[0050] (4) After the reaction is completed, the suspension is taken out and centrifuged at 8000 rpm for 10 minutes using a high-speed centrifuge to obtain a precipitate II; the precipitate II is added to deionized water and ultrasonically oscillated for 10 minutes, and centrifuged again to obtain a precipitate II; the precipitate II is then added to anhydrous ethanol and ultrasonically oscillated for 10 minutes, and centrifuged again to obtain a precipitate II, and the aforementioned oscillation and centrifugation operations are repeated until the supernatant is neutral after centrifugation, and each centrifugation is for 10 minutes. The solid product obtained after centrifugation is dried to obtain bismuth oxide powder.
[0051] (5) Sodium sulfide nonahydrate was dissolved in 80 ml of deionized water to prepare a solution I with a concentration of 0.01 mol / L. The solution I was stirred magnetically for 30 min, and the prepared bismuth oxide powder was added to the solution I. The molar ratio of bismuth to sulfur in the solution I was bismuth:sulfur=4:3. After mixing evenly, the solution I was transferred to a 200 ml reactor, and the reactor was placed in an oven and heated at a constant temperature of 160° C. for 720 min.
[0052] (6) After the reaction is completed, the suspension is taken out, and the reaction product is treated in the same manner as in step (4). After drying, a bismuth-based composite electrode powder, i.e., bismuth oxide / bismuth sulfide composite electrode material powder, is obtained.
[0053] The bismuth-based composite electrode powder prepared in this example was subjected to scanning electron microscopy and X-ray diffraction experiments, and the results were as follows: Figure 1 , 2 As shown, the bismuth-based composite electrode powder prepared in this example was subjected to a cycle stability test, and the results are shown in FIG. Figure 5 shown.
[0054] pass Figure 1 It can be seen that in the bismuth-based composite electrode material prepared in this embodiment, BO-BS is composed of BO( Figure 6 )'s two-dimensional lamellar shape is transformed into three-dimensional block-like stacks, which means an increase in its specific surface area.
[0055] pass Figure 2 It can be seen that in the bismuth-based composite electrode material prepared in this example, peaks of bismuth oxide and bismuth sulfide exist, so BO-BS is a composite of bismuth oxide and bismuth sulfide.
[0056] The bismuth oxide / bismuth sulfide composite electrode material powder is evenly mixed with conductive carbon black and PVDF in a mass ratio of bismuth oxide / bismuth sulfide composite electrode material powder: conductive carbon black: PVDF = 8:1:1 to obtain a mixture, NMP is added to the mixture until the slurry is thick enough to adhere to the wall, and the slurry is evenly mixed by magnetic stirring for 12 hours. Then, a homogenizer is used to apply the slurry to nickel foam, and a tablet press is used to press the bismuth oxide / bismuth sulfide composite electrode sheet at a pressure of 10 MPa for 30 seconds to obtain a bismuth oxide / bismuth sulfide composite electrode sheet, which is recorded as BO-BS.
[0057] A three-electrode system was built with BO-BS as the working electrode, HgO as the counter electrode, and platinum as the reference electrode. BO-BS was detected under the three-electrode environment, and the CV and CP diagrams of BO-BS under the three-electrode environment were obtained, as shown in the figure below. Figure 3 , 4 shown.
[0058] pass Figure 3 It can be seen that the CV curve of the BO-BS electrode has a typical “Duck” peak, which means that a reversible redox reaction occurs, which is consistent with the typical characteristics of battery behavior.
[0059] pass Figure 4 It can be seen that in 2Ag -1 At a current density of 1.34 W, the BO-BS sample has a specific capacitance of 305.57 Fg -1 .
[0060] Example 2
[0061] In this embodiment, bismuth-based composite electrode materials are prepared by the following method:
[0062] (1) 4.85 g of bismuth nitrate pentahydrate was placed in 10 ml of 0.8 mol / L nitric acid and stirred with a magnetic stirrer for 20 min to obtain a solution II.
[0063] (2) While the above solution II is being stirred, a 0.8 mol / L KOH solution is added dropwise to adjust the solution pH to 11.
[0064] (3) The solution II after pH adjustment in step (2) was stirred for 20 min using a magnetic stirrer, and then the solution II was transferred to a reaction kettle. The reaction kettle was placed in an oven and heated at a constant temperature of 120° C. for 720 min.
[0065] (4) After the reaction is completed, the suspension is taken out and centrifuged at 9000 rpm for 8 minutes using a high-speed centrifuge to obtain precipitate II; the precipitate II is added to deionized water and ultrasonically oscillated for 10 minutes, and centrifuged again to obtain precipitate II; the precipitate II is then added to anhydrous ethanol and ultrasonically oscillated for 10 minutes, and centrifuged again to obtain precipitate II, and the above oscillation and centrifugation operations are repeated until the supernatant is neutral after centrifugation, and each centrifugation is 8 minutes. The solid product obtained after centrifugation is dried to obtain bismuth oxide powder.
[0066] (5) Sodium sulfide nonahydrate was dissolved in 80 ml of deionized water and stirred with a magnetic force for 20 min to obtain a solution I. 2 g of the prepared bismuth oxide powder was added to the solution I. The molar ratio of bismuth to sulfur in the solution I was bismuth:sulfur=2:1. After mixing evenly, the solution I was transferred to a 200 ml reactor, and the reactor was placed in an oven and heated at a constant temperature of 160° C. for 720 min.
[0067] (6) After the reaction is completed, the suspension is taken out, and the reaction product is treated in the same manner as in step (4). After drying, a bismuth-based composite electrode powder, i.e., bismuth oxide / bismuth sulfide composite electrode material powder, is obtained.
[0068] The performance of the composite electrode material prepared in this example is similar to that of Example 1.
[0069] Example 3
[0070] In this embodiment, bismuth-based composite electrode materials are prepared by the following method:
[0071] (1) 4.85 g of bismuth nitrate pentahydrate was placed in 10 ml of 1.5 mol / L nitric acid and stirred with a magnetic stirrer for 40 min to obtain a solution II.
[0072] (2) While the above solution II is being stirred, a 5 mol / L KOH solution is added dropwise to adjust the solution pH to 14.
[0073] (3) The solution II after pH adjustment in step (2) was stirred for 40 min using a magnetic stirrer, and then the solution II was transferred to a reaction kettle. The reaction kettle was placed in an oven and heated at a constant temperature of 120° C. for 720 min.
[0074] (4) After the reaction is completed, the suspension is taken out and centrifuged at 10000 rpm for 15 minutes using a high-speed centrifuge to obtain precipitate II; the precipitate II is added to deionized water and ultrasonically oscillated for 10 minutes, and centrifuged again to obtain precipitate II; the precipitate II is then added to anhydrous ethanol and ultrasonically oscillated for 10 minutes, and centrifuged again to obtain precipitate II, and the above oscillation and centrifugation operations are repeated until the supernatant is neutral after centrifugation, and each centrifugation is for 15 minutes. The solid product obtained after centrifugation is dried to obtain bismuth oxide powder.
[0075] (5) Sodium sulfide nonahydrate was dissolved in 80 ml of deionized water and stirred with a magnetic force for 40 min to obtain a solution I. 2 g of the prepared bismuth oxide powder was added to the solution I. The molar ratio of bismuth to sulfur in the solution I was bismuth:sulfur=10:1. After mixing evenly, the solution I was transferred to a 200 ml reactor, and the reactor was placed in an oven and heated at a constant temperature of 160° C. for 720 min.
[0076] (6) After the reaction is completed, the suspension is taken out, and the reaction product is treated in the same manner as in step (4). After drying, a bismuth-based composite electrode powder, i.e., bismuth oxide / bismuth sulfide composite electrode material powder, is obtained.
[0077] The performance of the composite electrode material prepared in this embodiment is reduced to a certain extent compared with that in Example 1, but improved compared with Comparative Examples 1 and 2. This is because in this embodiment, the molar ratio of bismuth to sulfur is relatively different, and the amount of S grown in situ on bismuth oxide is relatively small, which affects the performance of the composite electrode material. Therefore, the molar ratio of bismuth to sulfur should not be too different, and it is preferred that the difference between the two does not exceed 5.
[0078] Comparative Example 1:
[0079] This comparative example adopts the same method as Example 1 to prepare the electrode material, except that in this comparative example, the electrode material is only bismuth oxide, not a composite electrode material. The electrode material in this comparative example is denoted as Bi 2 O 3 .
[0080] The electrode powder prepared in this comparative example was subjected to scanning electron microscopy and X-ray diffraction experiments, and the results were as follows: Figure 6 , 7 As shown, the electrode powder prepared in this example was subjected to a cycle stability test, and the results are shown in FIG. Figure 5 shown.
[0081] pass Figure 5 It can be seen that the BO-BS symmetrical capacitor has a 2Ag -1 After 3000 charge and discharge tests, the capacitance retention rate was 80.28%, which is higher than Bi 2 O 3 This shows that the bismuth-based composite electrode material prepared by the present invention can effectively improve the cycle stability and has excellent application performance.
[0082] pass Figure 6 It can be seen that the bismuth oxide sample is a two-dimensional square lamellar sample.
[0083] pass Figure 7 It can be seen that the electrode material prepared in this comparative example is indeed Bi 2 O 3 .
[0084] In a three-electrode environment, Bi 2 O 3 Test and obtain Bi under three-electrode environment 2 O 3 The CV and CP diagrams are as follows: Figure 8 , 9 shown.
[0085] pass Figure 8 It can be seen that the CV curve of the BO electrode has a redox peak reaction, and the reaction type is a redox reaction.
[0086] pass Fig. 9 It can be seen that in 2Ag -1 At a current density of 1.34 W, the BO sample has a specific capacitance of 61.95 Fg -1 .
[0087] It can be seen that the BO-BS sample has a higher specific capacitance than BO. This is due to the in-situ growth of S on bismuth oxide, which enhances the specific surface area, and the built-in electric field generated at the composite interface contributes additional electrons to improve conductivity. Therefore, the BO-BS composite electrode material exhibits excellent energy storage capacity and cycle stability, and can be used as an ideal supercapacitor electrode material.
[0088] Comparative Example 2:
[0089] In this comparative example, bismuth oxide powder was prepared by the same method as in Example 1, and bismuth sulfide powder was prepared by the following steps:
[0090] (1) 4.85 g of bismuth nitrate pentahydrate and 3.60 g of sodium sulfide nonahydrate were dissolved in 40 ml of water to obtain a bismuth nitrate solution and a sodium sulfide solution, respectively. The bismuth nitrate solution and the sodium sulfide solution were stirred in a water bath at 60° C. for 5 min.
[0091] (2) After the two solutions in step (1) are cooled, the bismuth nitrate solution and the sodium sulfide solution are mixed, stirred evenly, and then transferred to a reaction kettle, and the reaction kettle is placed in an oven and heated at a constant temperature of 160° C. for 720 minutes.
[0092] (3) After the reaction is completed, the suspension is taken out, and the suspension is centrifuged at 8000 rpm for 10 minutes using a high-speed centrifuge to obtain a precipitate; the precipitate is added to deionized water and ultrasonically oscillated for 10 minutes, and centrifuged again to obtain a precipitate; the precipitate is then added to anhydrous ethanol and ultrasonically oscillated for 10 minutes, and centrifuged again to obtain a precipitate, and the above oscillation and centrifugation operations are repeated until the supernatant is neutral after centrifugation, and each centrifugation is 10 minutes. The solid product obtained after centrifugation is dried to obtain bismuth sulfide powder.
[0093] (4) Bismuth oxide powder, bismuth sulfide powder, conductive carbon black and PVDF were mixed uniformly in a mass ratio of bismuth oxide: bismuth sulfide: conductive carbon black: PVDF = 4:4:1:1 to obtain a mixture, NMP was added to the mixture until the slurry was thick enough to adhere to the wall, magnetic stirring was performed for 12 hours to mix the slurry uniformly, and then a homogenizer was used to apply the slurry to nickel foam, and a tablet press was used to press the tablets at a pressure of 10 MPa for 30 seconds to obtain electrode sheets, which were recorded as BO+BS.
[0094] A three-electrode system was built with BO+BS as the working electrode, HgO as the counter electrode, and platinum as the reference electrode. BO+BS was detected under the three-electrode environment, and the CV and CP diagrams of BO+BS under the three-electrode environment were obtained, as shown in the figure below. Fig.10 , 11 shown.
[0095] pass Fig.10 It can be seen that the CV curve of the BO+BS electrode has a redox peak reaction, and the reaction type is a redox reaction. As the scan rate gradually increases, the redox peak shifts to both sides. This is due to the polarization phenomenon causing the redox peak to deviate from the equilibrium state.
[0096] pass Fig.11 It can be seen that in 2Ag -1 At a current density of 2.34 W, the BO sample has a specific capacitance of 24.06 Fg -1The reason why its performance is much lower than that of BO-BS is that it is a physical mixture. The mixed two-phase sample has a large interface resistance. Direct mixing does not have enough interface contact area and cannot generate a built-in electric field, thus limiting the efficiency of the electrochemical reaction.
[0097] By comparing Example 1 with Comparative Example 1, it can be seen that the bismuth-based composite electrode material prepared in Example 1 has a larger specific capacitance and discharge time. -1 ) condition, the maximum specific capacitance of BO-BS sample reaches 305.57Fg -1 , relative to Bi 2 O 3 61.95Fg -1 The bismuth-based composite electrode material has a significant increase in specific capacitance and discharge time, thanks to the sulfurization process that makes the two-dimensional Bi 2 O 3 Became a three-dimensional Bi 2 S 3 , thereby increasing the specific surface area of BO-BS and providing more conductive channels; at the same time, the built-in electric field generated by the bismuth oxide / bismuth sulfide heterojunction at the composite interface contributes additional electrons, increasing the conductivity and charge transfer speed.
[0098] Comparison between Example 1 and Comparative Example 2 shows that the bismuth-based composite electrode material prepared in Example 1 has a larger specific capacitance and discharge time. -1 ) condition, the BO-BS sample has the largest specific capacitance of 305.57Fg -1 , while the specific capacitance of BO+BS is only 24.06Fg -1 This is because in Comparative Example 2, Bi 2 O 3 and Bi 2 S 3 There is no interaction between them, resulting in an uneven structure after mixing, which affects the transmission efficiency of electrons and ions. 2 O 3 The conductivity of the electrode is poor, and direct mixing cannot improve the overall conductivity of the electrode, limiting the transmission of current. Furthermore, direct mixing does not have enough interfacial contact area to generate a built-in electric field, thus limiting the efficiency of the electrochemical reaction.
[0099] In summary, the present invention effectively improves the specific capacitance of the composite electrode material by preparing a bismuth-based composite electrode material, and still has a cycle stability rate of 94% after 1000 cycles, and has high cycle stability. At the same time, the bismuth-based composite electrode material is used in a pseudocapacitor supercapacitor as a positive electrode material, which can be combined with conventional negative electrode materials, showing good energy storage capacity and cycle stability, and can be used as an ideal supercapacitor electrode material.
[0100] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing a bismuth-based composite electrode material, characterized in that: The preparation method comprises the following steps: (1) dissolving sodium sulfide nonahydrate in water to obtain a solution I, adding bismuth oxide powder to the solution I to carry out a hydrothermal reaction to obtain a reaction product; (2) Centrifuging the reaction product obtained in step (1) to obtain a precipitate I, cyclically oscillating and centrifuging the precipitate I, and then drying the solid product obtained after centrifugation to obtain a bismuth-based composite electrode material.
2. The preparation method according to claim 1, characterized in that: In the step (1), the concentration of solution I is 0.01 mol / L. After bismuth oxide powder is added to solution I, the molar ratio of bismuth to sulfur in solution I satisfies bismuth:sulfur>1.
3. The preparation method according to claim 1, characterized in that: In the step (1), the hydrothermal reaction temperature is 160° C. and the reaction time is 720 min.
4. The preparation method according to claim 1, characterized in that: In the step (2), the precipitate I is alternately shaken and centrifuged using deionized water and anhydrous ethanol until the supernatant is neutral after centrifugation.
5. The preparation method according to claim 1, characterized in that: The bismuth oxide powder is prepared by the following steps: S1: adding bismuth nitrate pentahydrate into nitric acid and stirring well to obtain solution II; S2: Under stirring, adding KOH solution dropwise to the solution II obtained in step S1 to adjust the pH of the solution II to 11.0-14.0; S3: subjecting the solution II whose pH has been adjusted in step S2 to a hydrothermal reaction to obtain a reaction product; S4: centrifuging the reaction product obtained in step S3 to obtain a precipitate II, and alternately oscillating and centrifuging the precipitate II with deionized water and anhydrous ethanol until the supernatant after centrifugation is neutral, and drying the solid product obtained after centrifugation to obtain bismuth oxide powder.
6. The preparation method according to claim 5, characterized in that: In the step S1, the concentration of nitric acid is 0.8 mol / L-1.5 mol / L, and the solid-liquid ratio of bismuth nitrate pentahydrate to nitric acid is bismuth nitrate pentahydrate: nitric acid = 0.485 g: 1 ml.
7. The preparation method according to claim 5, characterized in that: In step S2, the concentration of the KOH solution is 0.8 mol / L-5 mol / L.
8. The preparation method according to claim 5, characterized in that: In step S3, the hydrothermal reaction temperature is 120° C. and the reaction time is 720 min.
9. A bismuth-based composite electrode material, characterized in that: The bismuth-based composite electrode material is prepared by the preparation method described in any one of claims 1 to 8. The bismuth-based composite electrode material is a composite of bismuth oxide / bismuth sulfide. The built-in electric field generated at the load interface contributes additional electrons to produce high conductivity.
10. The use of a bismuth-based composite electrode material according to claim 9 in a pseudocapacitor supercapacitor, characterized in that: The bismuth-based composite electrode material is used as a positive electrode material of a pseudocapacitive supercapacitor.
Citation Information
Patent Citations
Alpha-Bi2O3 loaded carbon material supercapacitor electrode material and preparation method thereof
CN111554519A